Com uma ajuda dos meus amigos: redes on line e off line de produção e mediação da música independente - Roberta Henriques de Brito (2011)
This research asserts that social networks are a support for independent music production. lt is understood that connections among different agents enhanced this type music production after the crisis of the phonographic industry in the mid-1990. These networks - both real and virtual- have been created and they are expanded by the increased use of technological resources that were used in the past to strengthen recordcompanies and now empower independent production. Such networks are established between musicians, their relatives and friends - usually bandsfirst audience - as well as musicians and producers - causing services and information exchanges - and between musicians and an unknown audience reached through the intemet. These networks are oriented by the logic of sharing and an acclaimed solidarity as a way of managing businesses and online relationships through the web.